Comprehensive Characterization of Furcraea selloa K. Koch Peduncle Fiber-Reinforced Polyester Composites—Effect of Fiber Length and Weight Ratio. (10th May 2022) - Divya, D.; Jenish, I.; Raja, S.
Abstract : Nowadays, scientists and researchers working on polymer composites are paying much attention to the discovery of prospective plant fibers in order to build a promising fiber-reinforced polymer composite. The present study investigated the efficacy of using a novel Furcraea selloa K. Koch peduncle fiber in reinforced composites, and the specific composite characterization was done to explore the absolute fiber length and weight ratio to accomplish superior composite properties. For that, peduncle fibers with different length-to-weight ratios were reinforced with unsaturated polyester and the corresponding composites were tested to decide the optimum fiber length-to-weight ratio for obtaining the utmost composite properties. The results indicated that the highest mechanical properties were allied with a composite reinforced with 30 mm fiber length and 30 wt.% with the tensile strength of 103.51 MPa and flexural strength of 144.65 MPa. While the remaining tested volumes showed decreased properties as compared to optimal, which might be due to debonding effects or less interfacial bonding as examined clearly in SEM images of fractured samples. Enhanced thermal stability with 390°C and relatively reduced water absorption rate was observed in the case of optimal range when compared to other testing dimensions. Moreover, the current study confirmed that FSPF composites possess promising comparable properties which would be a good alternative to existing synthetic composites.